Validation of secretory Immunoglobulin A (IgA) for early and efficient diagnosis of Pseudomonas aeruginosa lung infection: Validation of secretory Immunoglobulin - Zhou, Yingzhen; Zhang, Hao; Verma, Poonam; Samanta, Dipan; Verma, Manish Kumar; Kumar, Krishan (Cellular and Molecular Biology, 2023)
Pseudomonas aeruginosa is a gram-negative bacterium that is considered to be a major causal organism of nosocomial infection. This study brought data-specific evidence to reveal the efficacy of secretory Immunoglobulin A (IgA) measurement in diagnosing pulmonary P. aeruginosa infection and claims its validation as a diagnostic marker. This study has included controls and patients of Pseudomonas and grouped them into four, namely, controls, chronic cases, intermittent cases, and negative group. The last group, that is, the “Negative” group, is the ones who had a history of infection but currently showed negative blood culture. The level of sIgA was quantified in all the patients and the controls and then their status of pulmonary infection was determined by their blood culture. ANOVA and Pearson Chi-Square were employed for showing the association between sIgA and pulmonary infection. The mean value of salivary sIgA has been found the highest in chronic cases followed by Intermittent cases and Negative Infections. The boxplot diagram showed several parameters of sIgA quantification in each group and control. ANOVA and Pearson Chi-square (P<0.005) tests showed a significant association between sIgA level in saliva and pulmonary infection of P. aeruginosa. The ROC curve was plotted to determine the cut-off value of sIgA (sIgA≧13.09 U/ml) for efficient clinical diagnosis of pulmonary P. aeruginosa infection. The study has validated statistically that quantification of salivary sIgA can be used in clinical practice for early diagnosis of pulmonary infection of P. aeruginosa.